منهج الشيخ محمد أمين الإسلام في "تفسير نور‎ ‎القرآن" : السور الثلاث الأول أنموذجا - كمالي، محمد عبيد الحق (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The main purpose of this study is to explore the methodology of Shaykh Muhammad Aminul Islam in his Tafsir, Nurul Qur'an, as reflected in the first three surahs of the Qur'an. The researcher followed inductive and analytical approaches to explore the methods of Shaykh in his commentary of the Qur'an. It explains different aspects of his life, his education and work experiences. The study provides a brief introduction to this monumental Tafsir and its methodology, quoting the praises of the scholars on Shaykh Aminul Islam and his Tafsir. The study covered his methods in traditional and rational Tafsir, stand about thematic and analytical Tafsir, methods in the issues of sciences of Qur'an, particular methods about A'malul Qur'an (practices of the Qur'an), position on the issues of 'Aqidah and rebuttal on the anti-Islamic sects and group. The study reached certain conclusions, such as that the Tafsir covered traditional and rational methods. It is a synthesis of all explanations of the prominent scholars on the Qur'anic commentary. Hence, it is regarded to be the greatest Tafsir in Bangladesh. He presents solutions to family and social problems through the teachings of the Qur'an. He asserts that the only solution to all problems, religious and worldly, is by returning to the Message of God and following Divine guidance. Hence, regardless of a few negative features in his Tafsir, Shaykh Aminul Islam was able to present to mankind in general, and to Bengali speaking youths in particular, a precise and easy-to-read Tafsir in language and style, to make them understand the message of the Qur'an and guide them to the pure teachings of the Divine religion, so as to implement them in all avenues of life.